2021
DOI: 10.1177/23315024211035771
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation as a Bridge to Advance Practical and Theoretical Insights About Forced Migration Studies

Abstract: Modeling and Simulation (M&S) is a relatively unused research approach in forced migration studies. In most of its application areas, M&S is applied in several broad thematic policy-oriented topics: predicting human movement, humanitarian logistics, communicable diseases, healthcare, policing, and economics. More recently, there has been increased use of M&S in predicting human movement and health impacts resulting from climate change. Computer modeling has benefits for both policy and theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Policymakers normally see displacement as a one-off, short-term humanitarian problem, but it is a long-term situation that must be assessed holistically. Frydenlund (2021) suggested that modeling and simulation tools can incorporate the dynamic characteristics of migration and forced displacement and are an accessible way of integrating academia, practitioners and policymakers. Nevertheless, a gap remains between simulation techniques and migratory operations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Policymakers normally see displacement as a one-off, short-term humanitarian problem, but it is a long-term situation that must be assessed holistically. Frydenlund (2021) suggested that modeling and simulation tools can incorporate the dynamic characteristics of migration and forced displacement and are an accessible way of integrating academia, practitioners and policymakers. Nevertheless, a gap remains between simulation techniques and migratory operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frydenlund (2021) suggested that modeling and simulation tools can incorporate the dynamic characteristics of migration and forced displacement and are an accessible way of integrating academia, practitioners and policymakers. Nevertheless, a gap remains between simulation techniques and migratory operations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the modelling of environment-migration linkages [15]. In addition, ABM can be used in circumstances (where there is limited or no training data) to complement machine learning approaches (e.g., [16,17]) in regards to forecasting efficacy. Examples of ABM models in forced migration include models of events in refugee settlements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a possible avenue to mitigate these concerns, researchers and policy makers can lean on simulations to reflect systems of interest populated with simulated agents. The information created in these simulations can allow for a better understanding of the context of the system and its occupants, and help guide towards more informed participatory simulation designs [3]. Large language models (LLMs) can play a promising role in the ability to create useful narrative messaging that reflects both the emotional state of the individual that a narrative is based on and the context of the environment.…”
Section: Introductionmentioning
confidence: 99%